A novel in-vitro technique for shoot proliferation of Musa acuminata colla cv. grand naine and assessment of genetic stability of the micropropagated plants - Safarpour, Mahdi (2012)
This study was carried out to investigate the efficiency of using horizontal sections of a single shoot-tip as a novel technique for shoot induction and proliferation in Musa. acuminata cv. Grand Naine compared to the conventional and routine method of using single shoot-tip culture. The excised single shoot apices were cultured on MS basal medium supplemented with 0, 10, 20 and 30 μM of 6-benzylaminopurine (BAP) in combination with 1.0 μM 1-naphthaleneacetic acid (NAA) for six months with monthly subculture. The results revealed that mean number of proliferated shoots increased with subsequent subculture at all levels of BAP tested, reaching the highest mean of 23.6 shoots on 20 μM BAP at the sixth subculture with an average height of 1.7 cm per explant. In a parallel study, the excised single shoot-tips were initially cultured on MS medium supplemented with 10 μM BAP in combination with 1.0 μM NAA for one month. After one month, swelled explants were split into three horizontal sections numbered 1 to 3 from top to bottom. Each section was subcultured for two subsequent cycles onto MS media supplemented with the same concentration of BAP. The highest mean number of shoots per section (7.2) was attained on horizontal section number 2. In the next step, the regenerated shoots obtained from section 2, were isolated and cultured on MS medium supplemented with 0, 10, 20 and 30 μM of BAP in combination with 1.0 μM NAA for further shoot proliferation. BAP at the concentration of 10, 20 and 30μM produced an average of 6.2, 8.3 and 7.9 shoots per explant; respectively over four subsequent subcultures. This study showed that it is highly possible to regenerate plantlets from horizontal sections of a single shoot-tip. The results showed that from just one horizontal section of a single shoot-tip of banana cv. Grand Naine, 59.6 shoots can be produced after six months, while only an average of 23.7 shoots is obtained via direct regeneration through single shoot-tip culture of the same cultivar. RAPD fingerprinting of randomly selected micropropagated plants and their corresponding mother plants were carried out to assist the genetic stability oficropropagated plants obtained through single shoot-tip culture and horizontal sections of a single shoot-tip culture. The use of 14 decamer oligonucleotides primers resulted in amplification of 98 bands; ranging in size from 210 bp to 2460 bp in plants micropropagated through shoot- tip culture. Out of the 98, 23 bands were polymorphic corresponding to 23.5% polymorphism. Based on RAPD bands pattern, the pair wise values of month. After one month, swelled explants were split into three horizontal sections numbered 1 to 3 from top to bottom. Each section was subcultured for two subsequent cycles onto MS media supplemented with the same concentration of BAP. The highest mean number of shoots per section (7.2) was attained on horizontal section number 2. In the next step, the regenerated shoots obtained from section 2, were isolated and cultured onMS medium supplemented with 0, 10, 20 and 30 μM of BAP in combination with 1.0 μM NAA for further shoot proliferation. BAP at the concentration of10, 20 and 30μM produced an average of 6.2, 8.3 and 7.9 shoots per explant; respectively over four subsequent subcultures. This study showed that it is highly possible to regenerate plantlets from horizontal sections of a single shoot-tip. The results showed that from just one horizontal section of a single shoot-tip of banana cv. Grand Naine, 59.6 shoots can be produced after six months, while only an average of 23.7 shoots is obtained via direct regeneration through single shoot-tip culture of the same cultivar. RAPD fingerprinting of randomly selected micropropagated plants and their corresponding mother plants were carried out to assist the genetic stability of micropropagated plants obtained through single shoot-tip culture and horizontal sections of a single shoot-tip culture. The use of 14 decamer oligonucleotides primers resulted in amplification of 98 bands; ranging in size from 210 bp to 2460 bp in plants micropropagated through shoot- tip culture. Out of the 98, 23 bands were polymorphic corresponding to 23.5% polymorphism. Based on RAPD bands pattern, the pair wise values of similarity coefficients ranged from 0.89 to 0.97 between micropropagated plants and parental plant. However, for plants micropropagated through horizontal sections of single shoot-tip, a total number of 92 scorable bands were amplified with all being monomorphic and similar to the field grown control plants with a similarity index of 1.0. The present study showed that producing plants through micropropagation of a single shoot-tip over six subcultures resulted in 5.3% variation while no genetic variation was observed among micropropagated plants obtained through horizontal sections of a single shoot-tip. In the next step, proliferated shoots obtained through horizontal sections of a single shoot-tip were rooted on full strength MS media and MS medium supplemented with l.0, 3.0 and 6.0 μM IBA. In this study, full-strength MS medium with 6.0 μM IBA produced the highest mean number of roots per explant (14.8) with an average length of 3.5 cm. In the final stage, the rooted plantlets were transplanted to three types of growing medium comprising of sand + perlite (2:1 v/v), sand + perlite + vermiculite (3:2:1 v/v) and peat moss + perlite + vermiculite (3:2:1 v/v). After eight weeks, the highest survival (88.6%) was obtained in potting medium consisting Perlite + Vermiculite + Peat moss. Overall, the results proved the potential of horizontal sections of a single shoot-tip technique to supercede single shoot-tip culture in relation to mass multiplication in banana cv. Grand Naine. Additionally, the high genetic stability of micropropagated plants indicated the reliability of this method to produce large number of true to type plants in a short span of time.